A Mena Invasion Isoform Potentiates EGF-Induced Carcinoma Cell Invasion and Metastasis - Philippar, Ulrike (2008)
The spread of cancer during metastatic disease requires that tumor cells subvert normal regulatory networks governing cell motility to invade surrounding tissues and migrate toward blood and lymphatic vessels. Enabled (Ena)/vasodilator-stimulated phosphoprotein (VASP) proteins regulate cell motility by controlling the geometry of assembling actin networks. Mena, an Ena/VASP protein, is upregulated in the invasive subpopulation of breast cancer cells. In addition, Mena is alternately spliced to produce an invasion isoform, Mena(INV). Here we show that Mena and Mena(INV) promote carcinoma cell motility and invasiveness in vivo and in vitro, and increase lung metastasis. Mena and Mena(INV) potentiate epidermal growth factor (EGF)-induced membrane protrusion and increase the matrix degradation activity of tumor cells. Interestingly, Mena(INV) is significantly more effective than Mena in driving metastases and sensitizing cells to EGF-dependent invasion and protrusion. Upregulation of Mena(INV) could therefore enable tumor cells to invade in response to otherwise benign EGF stimulus levels.